Life cycle assessment of the production of stabilized lactic acid bacteria for the environmentally-friendly preservation of living cells. (20th May 2018) - Pénicaud, Caroline; Monclus, Vincent; Perret, Bruno; Passot, Stéphanie; Fonseca, Fernanda
Abstract: Among food ingredients, concentrates of lactic acid bacteria are widely used as starters for producing cheeses, fermented milks, meats, vegetables and beneficial health products (probiotics). The first objective of this study was to identify environmental hotspots of the production system of lactic acid bacteria concentrates. The second was to compare the impacts of the two scenarios of stabilization (freezing vs. freeze-drying). To fulfill these objectives, Life Cycle Assessment was performed. Since production processes damage lactic acid bacteria, the impact scores were weighted by the quality of the bacteria, i.e., their physiological state, to obtain meaningful comparisons. Storage and fermentation were the hotspots when bacteria were stabilized by freezing, whereas fermentation and freeze-drying were the hotspots when bacteria were stabilized by freeze-drying. By comparing different storage devices (laboratory vs. walk-in freezers), it was revealed that the device scale was a critical choice when storage was a hotspot. Surprisingly, no benefit was obtained by increasing the storage temperature of freeze-dried products from −20 °C to ambient temperature due to the high bacteria quality loss in such storage conditions. The scenario comparison (frozen vs. freeze-dried bacteria) highlighted the dependence of the results on storage time. The most eco-friendly scenario was frozen bacteria for storage periods of less than 2 months, whereas it was freeze-dried bacteria for storage periods of more than 7 months. Between 2 and 7 months, the conclusion depended on the indicators considered. This study demonstrated improvement options for the processes, including the energy efficiency of freeze-drying and the efficient use of steam and water, as well as optimized cleaning procedures for fermentation. It also highlighted the environmental benefit that could be obtained if the quality of the bacteria could be more efficiently preserved during freeze-drying and storage. This study provides valuable information concerning the preservation of microorganisms and the use of the cold chain. Highlights: Storage and fermentation were the hotspots in frozen bacteria scenario. Fermentation and freeze-drying were the hotspots in freeze-dried bacteria scenario. Scenarios comparison highlighted the dependence of the LCA results on storage time. The use of laboratory vs. walk-in freezer was critical when storage was a hotspot. Preservation of bacteria quality is crucial to get environmental benefit.